(untitled) (Journal of the College of Basic Education, 2025)
This research aims to identify the effect of using the interactive teaching model on the acquisition of mathematical concepts among first-year middle school students. The research sample consisted of (60) first-year middle school students for the second semester of the academic year (2024-2025), with (30) students in each of the experimental and control groups, where the two groups were rewarded in the variables of chronological age in months, previous knowledge in mathematics, previous academic achievement, intelligence level, and parents’ educational level. A test was prepared to measure the acquisition of mathematical concepts, which included (17) concepts distributed over three levels: defining the concept, applying it, and distinguishing it. The number of test items was (51) objective multiple-choice items with four alternatives for each item. The validity and reliability of the test were verified, as the reliability coefficient was (0.78) using the Kuder-Richardson equation. After completing the experiment, students in both groups were tested. The results, after analyzing the data using appropriate statistical methods, revealed a statistically significant difference between the two groups, favoring the experimental group, which achieved an 88% superiority in acquiring mathematical concepts compared to the control group. Based on these results, it is recommended that curricula be developed to include interactive learning activities that promote collaborative learning among students. Educational policies should be adopted that encourage the application of the interactive learning model in schools, while providing the necessary support. Training courses and workshops should also be organized for teachers to enhance interactive learning skills and manage interactive learning environments. Comparative studies should also be conducted on the impact of interactive learning and traditional learning on acquiring mathematical concepts at different educational levels, and digital interactive learning technologies, such as educational games and simulations, should be used to enhance understanding of complex mathematical concepts